Dissimilar laser lap welding of Mg and Al alloys using a CoCrFeNi medium-entropy alloy interlayer. (January 2023) - Zhou, Jun; Chen, Canyang; Zhou, Zhukun; Long, Hongyu; Jia, Jie; He, Lugui; Long, Yu
Highlights: High-entropy effect can effectively reduce Mg-Al intermetallic compounds in welding. Effect of laser power on the distribution of the HEAs and IMCs phase was investigated. HEAs distributed intermittently made the joint interface has the best performance. Abstract: Laser welding of Mg to Al dissimilar metals is of great significance in various industries, such as automobile, electrical, electronics, and energy systems, which promotes lightweight composite structure. However, Mg-Al intermetallic compounds (IMCs) have tremendous detrimental effects on the dissimilar metal joining of Mg to Al. In this work, dissimilar Mg/Al alloys joints with CoCrFeNi medium-entropy alloy (MEA) powders interlayer were achieved by the laser welding process, and the effect of different laser powers on the microstructure and mechanical properties of the joints was analyzed, reaching a maximum tensile shear strength of 100.12 MPa. The formation mechanism of the interface was investigated by experimental investigations and thermodynamic calculations. In addition, a numerical simulation of the laser welding process was carried out to reveal the temperature field of the molten pool and the flow change process. Based on the law of multi-component HEA phase formation, the interfacial metallurgical products were calculated and analyzed. The results of the energy dispersive spectroscopy show that the molten CoCrFeNi MEA powders reacted with Al to form Al-rich Al x CoCrFeNi phase, due to a more negative generation enthalpy compared to Mg-Al IMCs. With the increase of laser power, the Al-rich Al x CoCrFeNi phase mixed layer went through four states of agglomeration, continuity, interruption and dispersion, while the IMCs at the interface gradually increased and finally tend to be continuity. Due to the physical barrier of MEA and formation of Al-rich Al x CoCrFeNi phase, the formation of the Mg-Al IMCs phase was effectively suppressed, which improved the shear properties of the joints. The material- microstructure-property relations was established in this work, which facilitated the development of laser welding technology for Mg and Al alloys.